Online Learning: Practices, Perceptions, and Technology - Tess Miller; Kendra MacLaren; Han Xu (The Canadian Network for Innovation in Education (CNIE), 2020)
The purpose of this study was to examine factors influencing online learning given its rapid growth combined with the necessity to reduce attrition in online classes by providing quality instruction. This study was contextualized using the three elements of the community of inquiry (CoI) framework. We surveyed 93 students currently registered in online classes about their online learning experiences, perceptions, technological delivery of their course. Findings revealed that the majority of online courses were asynchronous using Moodle. There was a statistically significant difference between the three CoI dimensions and level of education where graduate students had more favourable online learning experience as measured by the CoI survey.